Phylogeny and Expression Analyses Reveal Important Roles for Plant PKS III Family during the Conquest of Land by Plants and Angiosperm Diversification - Xie, Lulu; Liu, Pingli; Zhu, Zhixin; Zhang, Shifan; Zhang, Shujiang; Li, Fei; Zhang, Hui; Li, Guoliang; Wei, Yunxiao; Sun, Rifei (Frontiers in Plant Science, 2016)
Abstract Polyketide synthases (PKSs) utilize the products of primary metabolism to synthesize a wide array of secondary metabolites in both prokaryotic and eukaryotic organisms. PKSs can be grouped into three distinct classes, type I, II, and III, based on enzyme structure, substrate specificity, and catalytic mechanisms. The type III PKS enzymes function as homodimers, and are the only class of PKS that do not require acyl carrier protein. Plant type III PKS enzymes, also known as chalcone synthase (CHS)-like enzymes, are of particular interest due to their functional diversity. In this study, we mined type III PKS gene sequences from the genomes of six aquatic algae and twenty-five land plants (one bryophyte, one lycophyte, two basal angiosperms, sixteen core eudicots, and five monocots). PKS III sequences were found relatively conserved in all embryophytes, but not exist in algae. We also examined gene expression patterns by analyzing available transcriptome data, and identified potential cis regulatory elements in upstream sequences. Phylogenetic trees of dicots angiosperms showed that plant type III PKS proteins fall into three clades. Clade A contains CHS/STS-type enzymes coding genes with diverse transcriptional expression patterns and enzymatic functions, while clade B is further divided into subclades b1 and b2, which consist of anther-specific CHS-like enzymes. Differentiation regions, such as amino acids 196-207 between clades A and B, and predicted positive selected sites within α-helixes in late appeared branches of clade A, account for the major diversification in substrate choice and catalytic reaction. The integrity and location of conserved cis-elements containing MYB and bHLH binding sites can affect transcription levels. Potential binding sites for transcription factors such as WRKY, SPL or AP2/EREBP may contribute to tissue- or taxon-specific differences in gene expression. Our data shows that gene duplications and functional diversification of plant type III PKS enzymes played a critical role in the ancient conquest of the land by early plants and angiosperm diversification. Keywords PKS III multigene family, CHS, STS, phylogenetic reconstruction, functional diversification, gene expression, cis-elements